Answer:
b. w= 8x^2-2y / y
Step-by-step explanation:
Given:
(2*x^2)/y = (w+2)/4
Isolating w, we get:
w = (8*x^2)/y - 2
Multiplying and dividing the second term in the right-side of the equality by y, we get:
w = (8*x^2)/y - 2*y/y
Subtracting the fractions:
w = (8*x^2 - 2y)/y
Answer:
28,389
Step-by-step explanation:
Answer:
(-3, -2)
Step-by-step explanation:
Look at the second equation, we can easily rearrange it to make x the subject.
x - 4y = 5
x = 4y + 5
Now lets put that into the second equation
2x - 2y = -2
2(4y + 5) - 2y = -2
6y + 10 = -2
6y = -12
y = -2
Now lets find x!
x = 4y + 5
x = 4(-2) + 5
x = -3
Now lets format the answer like the question says (ordered pair)
(-3, -2)
Recap: We used substitution and made an equation to work out one of the variables first, then found the second variable using the first.
Step-by-step explanation:
a power supply, a load suited to the power supply, and wiring as a conductor
Answer:
y = 36
Step-by-step explanation:
Everything in x-column is multiplied by 2, so everything in y-column is divided by 2 as per the inverse function.
=> 72/2
=> 36